Pengaruh Bermain Congklak Terhadap Memori Jangka Pendek Lansia Di Panti Pelayanan Sosial Lanjut Usia Dewanata Cilacap - Septiana, Putri; Ekowati, Wahyu; Setiyani, Rahmi (Journal of Bionursing, 2019)
Background. Elderly often have problems related to cognitive function, especially short-term memory. Short-term memory disorders can make the elderly become temperamental and face difficulties in social interaction. There are various ways to increase cognitive function. This study aimed to determine effect of playing congklak on short-term memory of elderly living in Dewanata Long Term Care Facility.Methods. This is a quasi experiment research with non-equivalen group design. Total sample was 28 people which divided into 2 group, control and intervention group. Short-term memory is measured by the digit span forward and backward, and the data were analyzed with the Wilcoxon test and Mann-Whitney test.Results. Majority of respondents were female and age 70 years old on average. There was a significant difference in pre and post test score in intervention group (p = 0.002), but it wasn?t found in control group (p = 0.739). Score difference in intervention group was significantly higher compared to those in control group (p = 0.001).Conclusion. Playing congklak can improve short-term memory of the elderly.